Redesigning Indonesia’s People’s School Policy: Structural Economic Lessons for Poverty Alleviation - Ninasapti Triaswati; Aprila Niravita; Noorimah Misnan (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2026)
This article critically examines Indonesia’s People’s School Policy as a socio-economic instrument for poverty alleviation, situating education reform within the broader structural economic context. The study employs a qualitative socio-legal and structural-economic approach, combining historical tracing of institutional design, policy document analysis, and a comparative review of education-linked poverty-alleviation programs in other developing countries. This methodological framework allows for a nuanced understanding of how education policy interacts with labor market segmentation, dependence on the informal sector, and unequal access to productive resources. The research identifies a significant gap in existing scholarship: most studies treat education policy as an isolated intervention, emphasizing access and enrollment while neglecting its integration with structural economic linkages. This narrow focus has limited the transformative potential of Indonesia’s People’s School Policy, which remains constrained by fragmented financing, weak institutional governance, and misalignment with long-term labor market strategies. Findings demonstrate that without structural economic alignment, expanded schooling opportunities fail to translate into sustainable livelihood outcomes. Comparative lessons from other developing contexts highlight the importance of inclusive financing models, community-based governance, and integration with long-term economic restructuring. These elements are crucial to ensuring that education reform contributes directly to poverty alleviation rather than reproducing existing inequalities. The article concludes that poverty alleviation through education requires more than expanding access; it demands a redesign that situates schooling within systemic economic change. By proposing a multidimensional framework that links education reform to structural economic restructuring, the study contributes to policy debates on equitable development. It offers a pathway for Indonesia to strengthen its poverty alleviation agenda.